IMPLEMENTASI DESIGN THINKING DALAM PERANCANGAN UI/UX APLIKASI JASA CATERING (JASCAT) - Okmayura, Finanta; Yolanda, Amalia; Wiranti (STMIK KAPUTAMA, 2024)
The catering business is an opportunity for entrepreneurs, especially for those with a cooking hobby. Currently, the catering business is highly competitive and rapidly growing with the technology era. The catering ordering process is still mostly through SMS or phone, and the lack of information and promotion makes the ordering and delivery process of food take a long time. This study aims to create a food ordering application online. This study applies Design Thinking to improve the user experience of the JASCAT application. The study uses the 5 stages of Design Thinking (empathize, define, ideate, prototype, test) to address user problems. UI/UX design is understood based on needs and solving user problems. Tests show that the JASCAT application designed with Figma has a score of 93 in the